1, 1′-Dihydroxy-2, 2′-biimidazoles: a new synthesis and crystal structure. Issue 1 (1st January 2015) - Tikhonov, Alexsei Ya.; Selivanov, Boris A.; Gatilov, Yurii V.
Graphical abstract: Abstract: An efficient method for the preparation of 1, 1′-dihydroxy-2, 2′-biimidazoles via cyclization of α, α′-dinitrones is reported. According to the X-ray crystal structure of the product, one ring adopts the 1-hydroxy form and the other ring exists in the N -oxide form.